If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(8x + 5) = -105 Reorder the terms: -5(5 + 8x) = -105 (5 * -5 + 8x * -5) = -105 (-25 + -40x) = -105 Solving -25 + -40x = -105 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + -40x = -105 + 25 Combine like terms: -25 + 25 = 0 0 + -40x = -105 + 25 -40x = -105 + 25 Combine like terms: -105 + 25 = -80 -40x = -80 Divide each side by '-40'. x = 2 Simplifying x = 2
| 20xcubed-4xsquared-72x= | | -4(6n-5)+3a= | | -2x+X=20-1 | | 5x-11=17+3x | | -2x-7+6(x+1)=-3x-6 | | X-2+x-3=57 | | 15.2d+7.24=-2.6-2.3d+11.59 | | 5(x-4)+6x=3(1-x) | | -9-3x=-5x+9 | | 1w-4=9-1w | | X+x=22+6 | | 28p=6p^2 | | .65X=9.10 | | 4-10k=34 | | x=4*60-160 | | 5+7(2x+11)+4x= | | 3x-6+8x=2x-3 | | W-4=9-w | | f(x)=-11x+3 | | 7x-7=4(2x-3) | | 12-12y-3(y+2)=4y+6-y | | x^3+40=13 | | 5e^9t=7e^8t | | 9+6=135 | | 2x+(-7+1x)=-1 | | 3x(x+2)=-18 | | -2(y+2)=3y | | 7s-8=64 | | y=17x^3 | | -14-8-6c=12-4c | | x=.25*150+40 | | 15-4(x+3)=19 |